Yemekhane Ve Hayvansal Kaynaklı Farklı Organik Katı Atıkların Birlikte Termofilik Ve Aşırı Termofilik Ortamda Havasız Arıtımının İncelenmesi - Dicle, Bahar (Fen Bilimleri Enstitüsü, 2012)
Katı atık kaynaklı kirlilikle oluşması muhtemel risk boyutunun artması, doğal kaynakların hızla tüketilmesi, sosyal ve ekonomik etkenlerin de varlığı nedeniyle katı atık yönetiminin önemi artmakta ve her geçen gün bu durum karmaşık hale gelmektedir. Mevcut bulunan düzenli depolama alanlarının kapasiteleri, hızla artan atık miktarıyla ters orantılıdır. Bunun yanı sıra bir çok Avrupa ülkesinde düzenli depolama hem yeterli alan sorunu hem de kontrol edilemeyen gaz emisyonları ile sızıntı suyu problemleri sebebiyle uygun bir atık yönetim metodu olmaktan çıkmıştır. Düzenli depolama yerine, çevresel etkileri daha kolay kontrol edilebilen diğer alternatif yöntemler (kompostlaştırma, anaerobik çürütme v.b.) de yaygın olarak kullanılma yolundadır. Organik katı atıkların anaerobik şartlar altında biyolojik olarak arıtılması sayesinde atığın organik madde içeriği azaltılmakta, besi maddeleri geri kazanılmakta, elde edilen son ürün toprak şartlandırıcı olarak kullanılmakta ve üretilen biyogaz da enerji kaynağı olarak değerlendirilmektedir. Katı atık, sürdürülebilirlik açısından değerlendirildiğinde yalnızca bir atık akımı olarak görülmeyip, aynı zamanda bir çok ürünün geri kazanılabileceği değerli bir kaynak olarak düşünülmelidir. Bu durum, katı atık yönetimini daha kapsamlı hale getirmenin önemini göstermektedir. Türkiye’de yaygın olan büyükbaş hayvancılığıyla elde edilen hayvan atığı ve yemekhane atığı biyolojik olarak parçalanabilir maddeler içermektedir. Büyükbaş hayvan atığı ve yemekhane atığının birlikte arıtılması, fazla katı madde içeriğine sahip bu iki atık türünün değerlendirilebilir birer kaynak olduklarını ve atıkların stabilizasyonunun sağlanmasının mümkün olduğunu göstermektedir. Yemekhane atığı hızlı ayrışabilir ve biyogaza kolayca dönüşebilir bileşikler içerir fakat tamponlama kapasitesi düşüktür ve bu durum asitleşme riskini arttırır. Büyükbaş hayvan atığının ise tamponlama kapasitesi yüksektir ve asitlerle ön arıtıma tabi tutulduğunda yüksek ayrışma performansı sağlanır. Bu durum bu iki atık türünün birbirlerini arıtmada desteklediklerini ve sistem performansını attırdığını göstermektedir. Bu çalışmada hayvan ve yemekhane atığı karışımlarının farklı işletme koşullarında metan ve hidrojen geri kazanımını sağlayacak anaerobik koşullarda arıtımı incelenerek, sistem performansının ortaya konmuştur. Bu çalışma, büyükbaş hayvan atıkları ile evsel nitelikli organik katı atık üretimi içerisinde önemli bir yeri olan yemekhane atıklarının birlikte % 50- % 50 oranında (UKM bazında) karıştırılarak, anaerobik şartlarda laboratuvar ölçekli anaerobik arıtılmasının deneysel olarak gerçekleştirilmesini ve sistem performansının incelenmesini kapsamaktadır. Ayrıca çalışmanın ileriki aşamalarında hayvan ve yemekhane atıklarının katı madde oranları sabit tutulup, aşı/substrat oranları değiştirilerek sistem performansının incelenmesini ve en uygun aşı/substrat oranının saptanmasını kapsamaktadır.

Solid waste management has gained great importance because of increasing potential risks that comes out of solid waste sources, consuming of natural sources and social and economic factors. This situation has become more complicated with each passing day. The capacities of current incineration plants and landfills is opposite to the increasing amount of wastes. In addition to this, waste management has become more difficult because of continiously reducing land fill capacities, site finding problems for new landfills, uncontroled gas emissions and leachate treatment. Instead of landfills, other alternative methods (compost, anaerobic digestion, etc.) are preferable because of simplicity in control of their environmental impacts. Thus, biological teratment of organic fraction of municipal solid waste under anaerobic conditions, organic matter content of waste is decreased, nutrients are recovered, end product is used as compost, produced biogas is considered as energy source. On the basis of growing needs of people, energy demand and enviromental problems have been increased and become a major problem. Solid waste shall be utilized to meet energy needs of people, to prevent enviromental problems and also to make our country and world more livable. Therefore, solid waste management has been more comprehensive day by day. Solid wastes which are produced as result of livestock industry and food wastes produced in cafeterias contains easily biodegradable substances. Treatmenf of livestock industry and food wastes in same system indicates that solid waste can be reused and stabilization of these kind of waste is also applicable. Livestock industry waste has high buffer capacity and when it is treated with acids it has high biodegredability capacity. On the other hand , kitchen waste which is easily biodegredable has low buffer capacity and high biogas production yield. During biogas production , acidification is one of the problem which is caused by low buffer capacity. In this study, the treatment of the mixture of cattle manure and kitchen waste in different operating conditions to ensure recovery of methane and hydrogen under anaerobic conditions is examined and system performance is presented. The main aim of co-digestion of cattle manure and kitchen waste is to supply balance different substrates in a mixture. Co-digestion of organic wastes has many advantages like raising the methane yield, balance of the system, creating a new type of waste and economic benefits. Anaerobic treatment with two stage has a great importance in energy efficiency. In two stage systems, it is possible to obtain biomethane and also biohydrogen which is clean. Hydrogen is a clean and efficient energy source and has been deemed as one of the most promising carriers of new energy for the future. From an engineering point of view, producing hydrogen by mixed cultures is generally preferred because of lower cost, ease of control, and the possible use of organic waste as feedstock. The biological hydrogen production has been intensively studied in recent decades. So far, most investigates of biohydrogen production are still confined to using pure carbohydrates and carbohydrate-rich wastewater. Nowadays, the large amounts of livestock manure, which come from cattle feedlots, poultry, and swine buildings, are causing a major environmental issue because it has become a primary source of odors, gases, dust, and groundwater contamination. The increasingly stringent requirements for pollution control on livestock manures are challenging the scientific community to develop new waste treatment strategies. Thus, there is a pressing need to develop nonpolluting and renewable energy source utilizing the organic waste (e.g., livestock manure). It is well known that anaerobic digestion had successfully been used for the disposal of manures to produce methane in the last two decades. Recently, an alternative strategy has been developed to convert livestock manures (e.g., dairy manures) to biohydrogen as a high value-added clean energy source instead of methane. However, little information is available on hydrogen production from dairy manure via the mixed anaerobic microbe. As far as we know, the hydrogen production is habitually accompanied with production of volatile fatty acids (VFAs), such as acetate, butyrate, and propionate, which are also an optimal feedstock for production of methane by anaerobic digestion. Provided that the biohydrogen production from dairy manure is further combined with the anaerobic digestion of the effluent from the producing hydrogen reactor that would be a one-stone two-bird paradigm, it not only produces a clean and readily usable biologic energy but also cleans up simultaneously the environment in a sustainable fashion. Biohydrogen production at extreme thermophilic temperatures has many advantages when comparing with mesophilic and thermophilic conditions. Extreme thermophilic conditions increase the hydrogen production yield, overcome pathogens. The organic waste consisted of Istanbul Technical University kitchen waste was crushed and mixed in particle size by mechanical pre-treatment to make it suitable for feeding to reactor and relatively homogenous. Fresh cattle waste was taken and fed to reactors without any pre-treatment. The type of waste that fed reactors was a mixture of cattle manure and milled halls waste and kept on +4 ̊C . Inoculum/substrate ratios on those systems are kept constant, the cattle manure and kitchen waste are treated together in different rates of solids (%1.7, 3, 6) to examine the system performance and the most suitable ratio of solid matter is determined. In addition, different inoculum/substrate (1:2, 1, 3:2, 2, 3) and different ratios of cattle manure and kitchen waste mixture (100:100, 75:25, 50:50, 25:100, 0:100) are used to examine the system performance and the most suitable ratio of mixture and ratio of inoculum/substrate are determined in another study. In this study, different amount of wastes mixtures were treated in four reactors. One of them is single stage thermophilic biomethane reactor, one of them is single stage extreme thermophilic biomethane reactor. The others which are called extreme thermophilic biohydrogen and thermophilic methane reactors, were operated in two stage systems. One sample was taken from reactors every two days. Samples were taken in two different ways as input and output of reactors, the day input sample was taken, output sample was not taken. And vice versa, the day output sample was taken, input sample was not taken. In that case, every input and output sample were taken in every 4 day average. In reactor BM70 the highest methane production is obtained as 811 mL CH4/day, VSS treatment efficiency as 13%, COD efficiency as 14%. Those values are very low in terms of methane production potential of organic waste . In the first part of study, inoculum/substrate ratios are taken as 1:2, 1, 3:2, 2, 3, and cattle manure and kitchen waste ratios as 1:1. On the other part of study, inoculum/substrate ratio is kept constant , but ratio of cattle manure and halls waste is taken as 100:100, 75:25, 50:50, 25:100, 0:100. The inoculum of extreme thermophilic biomethane reactor has the most reduction of COD, CODdis and VS when cattle manure and kitchen waste ratios is 1:1. When I/S is 3, the amount of producted biomethane is 35,4 mL according to COD removal. The inoculum of extreme thermophilic biohydrogen reactor has the most reduction of COD, CODdis and VS when cattle manure and kitchen waste ratios is 1:1. When I/S is 3, the amount of producted biohydrogen is 87,15 mL according to VS addition. The inoculum of two stage thermophilic biomethane reactor has the most reduction of COD, CODdis and VS when cattle manure and kitchen waste ratios is 1:1. When I/S is 3, the amount of producted biohydrogen is 201,42 mL according to COD removal. At this point, it can be said that a system operated in two stage is better in a high efficiency than a system operated in single stage. On two-stage system , it is able to achieve 88 m3 H2 and 742 m3 CH4 for per added tons. The reactions that occured in different steps of anaerobic threatment process with two-stage system were optimized in separate reactors, so the reaction speed and the amount of biogas can be increased. It can be said that two stages systems are more succesful than single stage systems, according to treatment performance. At extreme thermophilic conditions, biohydrogen productivity is high and it can be achieved in full-scale studies. In addition, it is an important competitive advantage to produce hydrogen called as one of the clean energy sources as today, except to produce methane in high efficiency with two-stage system. Finally, high amount of cattle manure and kitchen waste should be co-digested and supported by the government in Turkey. Full scale systems will provide high amount of energy.
The Co-digestion Of Kitchen Waste And Cattle Manure At Thermophilic And Extreme Thermophilic Conditions
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: anaerobik arıtım; havasız arıtma; birlikte arıtım; biyometan; biyohidrojen; termofilik; aşırı termofilik; büyükbaş hayvan atığı; yemekhane atığı; organik; tek kademeli; iki kademeli; anaerobic treatment; biomethane; biohydrogen; co-digestion; thermophilic; extreme thermophilic; cattle manure; kitchen waste; organic; one stage; two stages